The Assessment of the Demand of New Banking Tools in RA - Gevorgyan, Ruben; Hambardzumyan, Arev (Bulletin of Yerevan University G: Economics, 2015)
In the paper the preferences of RA residents towards financial assets were examined via the electronic survey to study the appropriateness of constructing a structured product with two underlying simultaneously: gold and silver. The results of the survey were analyzed in the work, according to which the residents of Armenia are inclined to trust gold, wish to participate in trade on world stock exchanges and are keen to diversification.
Keywords: structured product, commercial bank, deposit, currency, financial market, diversification, stock exchange